SATYAM SIVAM SUNDARAM: ESENSI KEBENARAN, KEBAJIKAN, DAN KEINDAHAN DALAM SIMBOL TARIAN SIVA NATARAJA SEBAGAI HUKUM SEMESTA - I Ketut Donder; Prasanthy Devi Maheswari; Jyothi Devi Krishnanandayani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Humans are the most perfect of all creatures, because only humans possess the ability to distinguish between the eternal and the transient. Furthermore, humans possess the awareness that they are not a material body, but the Atman, which is identical with Brahman. Advaita Vedanta theology and philosophy teach that Brahman pervades the universe. Therefore, Brahman and the Universe and all its contents are one. The Universe and all its contents are the material body of Brahman. Therefore, a practical understanding of Brahman can be observed through the Rtams, or Laws of Nature.Awareness of the Atman in humans is paramount in human life. Through awareness of the Atman, humans understand the existence of God behind all things. Awareness of the Atman makes humans wise, able to perceive God's presence in all things, as the Chandogya Upanisad states,